Genetic Engineering of Potato (Solanum tuberosum L.) IPB CP2 Variety with OsGERLP Gene: Genetic Transformation of Potato (Solanum tuberosum L.) IPB CP2 Variety with OsGERLP Gene - Nurhasanah, Eka; Tjahjoleksono, Aris; Miftahudin, M. (Departemen Biologi, Institut Pertanian Bogor, 2025)
High dissolved aluminum (Al) content in acidic soil can inhibit root elongation, especially in plants sensitive to Al. The OsGERLP gene is known to be an Al tolerance gene in rice, but the role of this gene in other plants is not yet known. Introduction of the OsGERLP gene to potato cv. IPB CP2 mediated by Agrobacterium tumefaciens has been succesfully conducted. When using leaf explant, the transformation and regeneration efficiencies were 72.62 and 17.24%, respectively. However, transgene introduction using internode explant increased transformation and regeneration efficiencies to 71.3 and 87.65%, respectively. PCR-based transgene integration analysis showed that all transgenic clones contain the OsGERLP gene under the control of the 35ScaMV promoter, which was indicated by the formation of 1500 bp amplicons. Transgenic clones have been in vitro tested for Al stress using liquid MS medium with different pH and Al content. The result showed that all transgenic clones have higher tolerance to Al compared to non-transgenic plant. Morphological analysis showed that transgenic clones performed better in all parameters including plant height, total root length, number of roots, shoot and root fresh weight, shoot and root dry weight. The transgenic clones can potentially be developed as potato transgenic lines tolerant to Al toxicity.